Deploying Affect Inspired Mechanisms to Enhance Adaptive Agent Decision Making and Strategic Communication in Complex Environments - Siti Azrehan Aziz; Astri Indah Juwita; I Putu Yesha Agus Ariwanta (Takaza Innovatix Labs Ltd., 2026)
This study investigates the integration of affect-inspired mechanisms in agent-based systems to enhance decision making and strategic communication in complex environments. The research aims to evaluate whether agents equipped with emotional appraisal architectures outperform standard rational agents in uncertain, dynamic scenarios. A mixed-method approach was employed, incorporating both simulation-based experiments and quantitative performance analysis. Agents were assigned specific roles principal, goal-lover, and resource lover within an asymmetric decision-making task to observe the influence of affect on strategic adaptation and inter-agent coordination. Results demonstrate that agents with affective capabilities achieved higher average scores, improved role-based consistency, and exhibited context-sensitive prioritization strategies. The data reveal that affect equipped agents can facilitate more cooperative and adaptive behaviors, particularly in scenarios requiring rapid goal reassessment and relational dynamics. These findings support the design of emotionally-aware artificial intelligence systems that are more aligned with human-like reasoning and capable of functioning effectively in complex, high stakes environments